Answer:
x=0.75
Step-by-step explanation:
Hope this helps!
To find the factor a a polynomial from its roots, we are going to seat each one of the roots equal to
![x](https://tex.z-dn.net/?f=x)
, and then we are going to factor backwards.
We know for our problem that one of the roots of our polynomial is -3, so lets set -3 equal to
![x](https://tex.z-dn.net/?f=x)
and factor backwards:
![x=-3](https://tex.z-dn.net/?f=x%3D-3)
![x+3=0](https://tex.z-dn.net/?f=x%2B3%3D0)
![(x+3)](https://tex.z-dn.net/?f=%28x%2B3%29)
is a factor of our polynomial.
We also know that another root of our polynomial is
![1+ \sqrt{2}](https://tex.z-dn.net/?f=1%2B%20%5Csqrt%7B2%7D%20)
, so lets set
![1+ \sqrt{2}](https://tex.z-dn.net/?f=1%2B%20%5Csqrt%7B2%7D%20)
equal to
![x](https://tex.z-dn.net/?f=x)
and factor backwards:
![x=1+ \sqrt{2}](https://tex.z-dn.net/?f=x%3D1%2B%20%5Csqrt%7B2%7D%20)
![x-1= \sqrt{2}](https://tex.z-dn.net/?f=x-1%3D%20%5Csqrt%7B2%7D%20)
![x-1- \sqrt{2}=0](https://tex.z-dn.net/?f=x-1-%20%5Csqrt%7B2%7D%3D0%20)
![(x-(1+ \sqrt{2})=0](https://tex.z-dn.net/?f=%28x-%281%2B%20%5Csqrt%7B2%7D%29%3D0%20)
(
![(x-(1+ \sqrt{2} ))](https://tex.z-dn.net/?f=%28x-%281%2B%20%5Csqrt%7B2%7D%20%29%29)
is a factor of our polynomial.
We can conclude that there is no correct answer in your given choices.
Answer:
it is the 7th
Step-by-step explanation:
plz take my answer
Answer:
<em>The square root of 36/196 is </em><em>3</em><em>/</em><em>7</em><em>.</em>
<em>The </em><em>square</em><em> root</em><em> of</em><em> </em><em>3</em><em>6</em><em>/</em><em>1</em><em>6</em><em>9</em><em> </em><em> </em><em>is </em><em> </em><em>6</em><em>/</em><em>1</em><em>3</em><em>.</em>